Trafficking of women and children : Article 7 of the Rome Statute - Aston, Joshua Nathan (New Delhi, India : Oxford University Press, 2016)
Joshua Nathan Aston studies the severity of human trafficking, its transnational networks, and the impact of international criminal and humanitarian laws in dealing with the crime. Analysing global statistics in detail, he provides a perspective on the effectiveness of the UN protocols and examines the role of the International Criminal Court, with a focus on Article 7 of the Rome Statute.
Introduction : Trafficking and the Rome Statute -- Trafficking of women and children : basic concepts -- The legal prohibition -- Establishing an effective legal response -- International institutions vis-à-vis crimes against humanity -- The feasibility of prosecution of crimes against humanity by the International Criminal Court -- Enforcement mechanism of the International Criminal Court.
Includes bibliographical references and index.
Keywords: Rome Statute of the International Criminal Court -- (1998 July 17); Human trafficking -- Law and legislation; Women -- Crimes against; Children -- Crimes against